Por um ordenamento cívico do território: uma reflexão crítica sobre o planejamento urbano e regional a partir da obra de Milton Santos - LEITE, Gabriel Carvalho da Silva (Universidade Federal do Pará, 2020)
An important expression of the Brazilian social thought in the 20th century, the work of the geographer Milton Almeida dos Santos (1926-2001) is widely known for its contributions to the critical theory of space, to the study of the urbanization in “underdeveloped” countries and to the interpretation of the Brazilian territory in the period of globalization. The present work seeks to investigate a less recurrently approached aspect of the miltonian work, namely its contributions to the field of the urban and regional planning. In the light of a historical-structural interpretation method and based on a set of main (bibliographic survey, documentary survey and analysis and content analysis) and complementary (contextual analysis and semi structured interviews) methodological procedures, the miltonian contributions to this field are investigated from two perspectives, one of diachronic character and the other of synchronic nature. In the diachronic perspective, the historical-genetic aspects of urban and regional planning in Milton Santos‟ work are highlighted, in order to elucidate the greater or lesser presence of this theme along the professional and intellectual trajectory of the geographer. On the other hand, from the synchronic perspective, the miltonian thought is understood in its contemporary insertion in the field of urban and regional planning, considering the important transformations it went through in the recent decades. It is concluded that Milton Santos can be considered one of the intellectual expressions of Brazilian social thought that has dedicated itself to think about urban and regional planning, and that for two reasons. Firstly, because this problem was recurrent in his vast academic production and in the technical and political-administrative activities that he exercised in different institutions. Secondly, because the miltonian thought is today an important theoretical-conceptual system that offers to researchers and planners an original analytical perspective (the political economy of the territory) and a propositional and operational perspective (the civic territorial model); contributions that have been inspiring Brazilian academic production at postgraduate level in the problematization and interpretation of issues concerning urban and regional planning in the Amazon. This reaffirms the relevance and timeliness of Milton Santos‟ intellectual legacy to the field of city and regional planning.